Permanent Missions to the United Nations, No. 298 - United Nations (United Nations, 2008)
Permanent Missions to the United Nations lists the names, addresses and phone numbers of all representatives to the United Nations. This publication is written in conjunction with the Protocol and Liaison Service and is released in English.